Memoria y derechos humanos en pandemia: la experiencia de "Las/os estudiantes vamos a los Juicios" - Silveyra, Malena (2021)
The emergence of coronavirus in early 2020 meant the challenge of adapting university education designed for face-to-face attendance to different modes of virtuality. This article analyzes the particular experience of "Las/os estudiantes vamos a los Juicios" workshop at UBA's Law School. Based on the attendance at the hearings of the trials against genociders that have been taking place since 2006 in Argentina, this readjustment involved double-effort planning. In light of the different proposals made in 2020 and 2021, the tensions between virtuality-presence and the need to advance in the process of building Memory, Truth and Justice are analyzed.